MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Azizah Mursyidah; Riani Heryanti (SAHID DEVELOPMENT JOURNAL, 2023)
This community service aims to determine the extent of understanding of Islamic Economics and Business education and the target of this service to the people of Karehkel Village, Leuwiliang District, Bogor Regency, West Java Province. In this community service, activities are carried out based on transparency and participation methods so that the community can participate fairly in this activity. The result of this community service is that this service is carried out by providing an introduction to Islamic economics and business which is carried out with presentations, providing tutorials, discussions, and practices around material about Islamic economics and business education. Education is one of the basic capital of development, so education is an investment or the main capital in the future. Planning for Islamic Economics education and business practices based on sharia principles today is no longer a necessity, but has become a reality and is increasingly widespread. Economic institutions and Islamic business products are emerging and growing in various parts of the world, even in the midst of non- Muslim communities. Likewise educational planning and training that prepares the personnel for it. Scientific studies on the concept of Islamic economics and business are also continuing and deepening. With this community service, it can be concluded that Islamic education planning is essentially a decision-making process on a number of alternatives regarding the targets of the methods that will be implemented in the future in order to achieve the desired goals and monitoring and evaluating the results of their implementation. And the importance of education to bring the seeds of renewal for the development of society in an effort to improve the quality of life of a prosperous society and it is very necessary to have new and wider knowledge.